2021
DOI: 10.2147/jir.s326559
|View full text |Cite
|
Sign up to set email alerts
|

PLAUR as a Potential Biomarker Associated with Immune Infiltration in Bladder Urothelial Carcinoma

Abstract: Background Bladder urothelial carcinoma (BLCA) is one of the most lethal and aggressive malignancies of genitourinary system that affects human health. The urokinase plasminogen activator receptor (PLAUR) plays essential roles in tumorigenesis and immune modulation, and its aberrant expression is closely correlated with cancer progression. However, whether PLAUR has the potential to be one promising biomarker or immunotherapy target for BLCA is unknown. Methodology Vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Oncostatin M (OSM) has been identified as significantly linked to tumor progression, potentially serving as a biomarker to predict OS in hepatocellular carcinoma [ 37 ]. Elevated levels of urokinase-type plasminogen activator receptor (PLAUR) was detected in bladder urothelial carcinoma, showing a correlation with the abundance of 28 types of tumor-infiltrating lymphocytes [ 38 ]. Increased expression of PLAUR indicated an unfavorable prognosis in glioma [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Oncostatin M (OSM) has been identified as significantly linked to tumor progression, potentially serving as a biomarker to predict OS in hepatocellular carcinoma [ 37 ]. Elevated levels of urokinase-type plasminogen activator receptor (PLAUR) was detected in bladder urothelial carcinoma, showing a correlation with the abundance of 28 types of tumor-infiltrating lymphocytes [ 38 ]. Increased expression of PLAUR indicated an unfavorable prognosis in glioma [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating studies have revealed the oncogenic significance of PLAUR. For example, recent studies have elucidated its pivotal role in the proliferation, invasion, and metastasis processes of esophageal cancer ( Xie et al, 2023 ), breast cancer ( Zhang et al, 2023 ), bladder urothelial carcinoma ( Liu et al, 2021 ), and prostate cancer ( Kimura et al, 2020 ). Zhang et al (2022) have demonstrated in vitro and in vivo that PLAUR promotes the malignant process of gastric cancer by affecting the cell cycle, apoptosis, and EMT.…”
Section: Discussionmentioning
confidence: 99%
“…PLAUR , a membrane protein also known as urokinase-type plasminogen activator receptor (UPA-R, CD87), is mainly responsible for the expression of cellular plasmin, which promotes cell extravasation and tissue invasion. Studies have found that PLAUR is closely related to the occurrence and prognosis of a variety of malignant tumours ( 22 , 23 ). Furthermore, PLAUR gene polymorphism also affects the prognosis of tumours, with SNPs in the gene found to be associated with disease-free survival in breast cancer ( 24 ).…”
Section: Discussionmentioning
confidence: 99%